Neuromyths in Education: Prevalence Among South Indian School Teachers - Jeyavel, Sundaramoorthy; Pandey, Vijyendra; Rajkumar, Eslavath; Lakshmana, Govindappa (Frontiers in Education, 2022)
The current study aimed to find out the existence of Neuromyths among school teachers in the South Indian States. An online survey was carried out to assess the school teachers’ general understanding of the brain and their belief on selected seven Neuromyths statements. 504 High school and Higher secondary school teachers from South India participated in this study. On average, 65.5% of teachers have shown their belief towards more than two of the Neuromyths. 84% of the participants have believed the learning style myths. This point out the difficulty of teachers in distinguishing factual information from non-scientific facts or myths. Therefore, there is an important need for involving interdisciplinary conversation which can reduce misunderstandings among teachers in the future.